1999
DOI: 10.1016/s0002-9440(10)65276-5
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1 Fails to Stimulate Wound Healing and Impairs Its Signal Transduction in an Aged Ischemic Ulcer Model

Abstract: Clinical trials of exogenous growth factors in treating chronic wounds have been less successful than expected. One possible explanation is that most studies used animal models of acute wounds in young animals, whereas most chronic wounds occur in elderly patients with tissue ischemia. We described an animal model of age- and ischemia-impaired wound healing and analyzed the wound-healing response as well as the transforming growth factor (TGF)-beta1 effect in this model. Rabbits of increasing ages were made is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 54 publications
(61 reference statements)
6
88
0
Order By: Relevance
“…Yet, numerous clinical studies of recombinant growth factors used to treat chronic wounds have reported disappointing results [68]. Proteolytic degradation of growth factors and unresponsive growth factor signaling cascades are thought to contribute to an impaired wound healing response [69,70]. Interestingly, consistent with those results, we found that cellular proliferation, migration, and angiogenesis were significantly impaired when the conditioned medium was depleted of exosomes by ultracentrifugation.…”
Section: Discussionsupporting
confidence: 84%
“…Yet, numerous clinical studies of recombinant growth factors used to treat chronic wounds have reported disappointing results [68]. Proteolytic degradation of growth factors and unresponsive growth factor signaling cascades are thought to contribute to an impaired wound healing response [69,70]. Interestingly, consistent with those results, we found that cellular proliferation, migration, and angiogenesis were significantly impaired when the conditioned medium was depleted of exosomes by ultracentrifugation.…”
Section: Discussionsupporting
confidence: 84%
“…(TGF-␤1 is increased more in the early phases of wound healing, which are prolonged in ischemic ears). In contrast, rabbit ear ulcers in aged animals failed to show any significant increase in TGF-␤1 mRNA under ischemic and nonischemic conditions until day 12, a finding consistent with the greater delay in wound healing in the aged animals [3]. Further research into the signaling pathway of TGF-␤ showed that aged human dermal fibroblasts have altered TGF-␤ signal transduction because of downregulated receptors.…”
Section: Hypoxia and Tgf-␤-1mentioning
confidence: 58%
“…The aged have an altered response to hypoxia, and wound healing is markedly delayed. The ischemic rabbit ear model evidences such delay in aged animals, and the depression was shown to be evident even in middle-aged rabbits [3]. By maintaining chronic ischemia in the rabbit ear model, a chronic wound model can beproduced in which there is minimal healing, even after 26 days [32].…”
Section: Impact Of Aging On Hypoxic Stimulusmentioning
confidence: 98%
See 1 more Smart Citation
“…This likely reflects a reduction in the number of capillaries as well as a reduction in mitochondrial enzyme activity 68 . Animal models (rabbit 69 and mouse 69,70 ) have suggested that aging and ischemia have an additive effect on disruption of wound healing. Consequently, the potential benefit of increasing tissue oxygen tension during surgical wound repair in older patients should be further evaluated.…”
mentioning
confidence: 99%